Effectiveness of Green Sukuk in Indonesia: Emission Measurement, Sharia Law, and Transparency - Amal Zainun Naim; Yustafad; Muhammad Fathur Reza (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Purpose – This study critically evaluates the effectiveness of Indonesia's Green Sukuk as a sustainable financing instrument by integrating the perspectives of maqāṣid al-sharīah, regulatory governance, and global transparency standards. It addresses the gap between normative claims and implementation, particularly in terms of impact measurement and the risks of greenwashing. Design/Methods/Approach – A qualitative-normative approach, incorporating documentary analysis, is employed. Primary documents include national regulations, Green Sukuk reports, and Sharia fatwas. Data were analyzed thematically using NVivo to map the interconnections between Sharia objectives, sustainability governance, and reporting frameworks. Findings – Green Sukuk demonstrates strong potential for mobilizing ethical capital. However, its effectiveness is constrained by non-standardized environmental impact measurement, partial regulatory harmonization, and weak independent verification. While global standards (e.g., IFRS Sustainability Disclosure Standards) are conceptually aligned with maqāṣid al-sharīah, their operationalization requires stronger Sharia governance oversight and enforcement mechanisms to ensure substantive, not just symbolic, sustainability outcomes. Research Implications/Limitations – The study provides a critical integrative framework for policymakers and scholars. Its reliance on documentary data is a limitation, calling for future empirical validation at the project level. Originality/Value – This paper offers a novel integrative framework that bridges Islamic finance ethics (maqāṣid al-sharīah) with global sustainability governance, contributing to both academic discourse and practical policy design for credible Sharia-compliant green finance.